PENINGKATAN PERFORMA KINERJA PELAYANAN INDUSTRI TELEKOMUNIKASI MENGGUNAKAN FILOSOFI KAIZEN DAN VISUAL STREAM MAPPING STUDI KASUS PT. TELKOM INDONESIA REGIONAL II JAKARTA PUSAT - Arief Nugroho; Choesnul Jaqin (Operations Excellence: Journal of Applied Industrial Engineering, 2017)
PT. Telkom Indonesia is the largest telecommunications provider in Indonesia which has been serving the country for about 160 years. As the company grows, the range of service it provided also improved, starting from just a fixed line provider to internet and IP TV. Telkom always follows what its customers need. However, the occurrence of problem cannot be avoided. Problems can always appear from many aspects either it is controllable and uncontrollable.  To provide the best service, Telkom offers the services to fix and repair any problem faced by its customers, but this is not an easy task, until today Telkom has not yet been able to meet the Service Level Guaranteed which it promised to its customers. There are also many outstanding tickets unresolved even when Telkom has many human resources. Therefore, this research aims to reduce the time required to fix problems and solve tickets through lean methodology for service by implementing value stream mapping and eliminating as well as improving the non-value-added activities and non-value-added but necessary. Through this approach, this paper assumes that currently it is highly possible to achieve the service level guaranteed as long as improvements are made.